Visfatin level and gestational diabetes mellitus: a systematic review and meta-analysis. (3rd September 2021) - Jiang, Yong-Kuan; Deng, Hai-Yan; Qiao, Zeng-Yong; Gong, Fang-Xiao
Abstract: It is reported that elevated visfatin level is associated with gestational diabetes mellitus (GDM). However, the relationship between visfatin level and GDM remains controversial. The aim of our study was to systematically review available literature linking visfatin to GDM for a comprehensive understanding of the relationship between circulating visfatin level and GDM in human. PubMed, The Cochrane Library and Web of Science were searched for studies published up to July 2020. Standard mean difference with 95% confidence interval was calculated to evaluate the relationship between visfatin level and GDM using the Review Manager 5.3 and Stata 12.0. The evidence indicated that no significant difference was observed in the level of circulating visfatin between the women with GDM and normal glucose tolerance, suggesting circulating visfatin level is not independently related to GDM. Nevertheless, visfatin is involved in the development of GDM in obese women.